2008
DOI: 10.1292/jvms.70.197
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Responses in Camels (Camelus bactrianus) Vaccinated with Brucella abortus strain 19 Vaccine

Abstract: ABSTRACT. In the present study, we determined the levels of cytokines produced by camel (Camelus bactrianus) peripheral blood mononuclear cells (PBMCs) in response to live attenuated Brucella abortus (B. abortus) S19 vaccine. Seven camels were vaccinated with commercial B. abortus S19 vaccine, and their cytokine responses were determined using a real-time PCR assay. Cytokine responses to B. abortus S19 were examined at 6 hr, 48 hr and 1, 2 and 3 weeks post-vaccination. Serological tests were performed to furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…These findings are in accordance with other studies that have estimated IL-10 production following Brucella infection (Hoover et al, 1999;Pasquali et al, 2001). Similar findings were also recorded in camels (Camelus bactrianus) experimentally vaccinated with B. abortus strain 19 (Odbileg et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings are in accordance with other studies that have estimated IL-10 production following Brucella infection (Hoover et al, 1999;Pasquali et al, 2001). Similar findings were also recorded in camels (Camelus bactrianus) experimentally vaccinated with B. abortus strain 19 (Odbileg et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…This finding coincided with that of Saunders et al (1993) who found that IL-6 titres decreased after the peak of infection, falling to baseline levels before these chronic infections were eradicated. On the other hand, Odbileg et al (2008) recorded a significant increase in IL-6 levels in camels vaccinated with B. abortus strain 19 compared with non-vaccinated camels. This result suggests that the state of infection could affect the cytokine level.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, the inflammatory cytokines were elevated in camel as result of infection or vaccination. The upregulation of the cytokines IL-6, IFN-γ, IL-10, interleukin-1α and β (IL-1α and β) and the TNF-α was detected with real time polymerase chain reaction (PCR) in camel vaccinated with strain 19 of Brucella abortus [38]. The increases in the level of the same cytokines were also detected in camel infected with Mycobacterium avium subspecies paratuberculosis (MAP) [39].…”
Section: The Cytokinesmentioning
confidence: 99%